ORGANIZATIONAL CITIZENSHIP BEHAVIOR THROUGH SELF-EFFICACY AND INTERPERSONAL COMMUNICATION IN HIGHER EDUCATION - Griet Helena Laihad; Purnama Pasande; Henny Suharyati (Jurnal Info Sains : Informatika dan Sains, 2022)
Research on Organizational Citizenship Behavior (OCB) has been carried out by many researchers but not many have conducted research on higher education students. This study develops the concept of student OCB in terms of Self-efficacy and Interpersonal Communication aspects. The data were taken from 104 students in STT Star’Lub at Luwuk Banggai. The data processing method uses regression analysis and Structural Equation Modeling (SEM). The results showed that the student Self-efficacy with the dimensions of self-motivation to perform tasks and the Interpersonal Communication of students with the dimension of showing empathy were the most influential things in increasing student OCB. Therefore, it could be concluded that in developing student OCB, Self-efficacy and Interpersonal Communication should be taken into consideration